An integrated finite element and finite volume code to solve thermo-hydro-mechanical problems in porous media - Gosavi, Shekhar Vishwanath (Kansas State University, 2006)
The objective of the thesis is to provide a fully coupled thermo-hydro-mechanical (THM) tool, T2STR, which enables quantitative understanding and prediction of thermal as well as mechanical effects on flow in the porous media under multiphase conditions. This is achieved by incorporating a finite element based hydro-thermo-mechanical stress capability into the well-established IFDM (Integrated Finite Difference Method) based flow simulation code TOUGH2. TOUGH2 is a program for calculation of multi-phase, multi-component, non-isothermal flow in porous media. It implements several equation of state modules to represent different fluid mixtures. The dual mesh technique is natural for combining both discretization methods and is used innovatively and effectively. A generalized approach is developed to accommodate the switching of variables implemented in TOUGH2 to adapt the phase changes. The forward coupling is achieved by using the thermal, hydrostatic, and poroelastic effects in the stress calculations. The backward coupling includes the effect of strain on the fluid flow. T2STR also allows the user to study the variation in porosity, permeability and capillary pressure as function of mean effective stress in the porous media. Multiple materials can be used to model the reservoir in T2STR, parallel to the implementation in TOUGH2. T2STR is implemented to carry out as a fully coupled, one way coupled (only deformation as function of hydro-thermal effects), or original TOUGH2 implementation. It provides the ability to switch on and off the thermal and/or poroelastic effects. T2STR is developed to model the fractured porous media using discrete fractures. The modeling of fractured porous media is limited to a staggered coupling approach. The fluid parameters like permeability, porosity are modified based on the stresses and/or aperture changes due to deformation. A set of verification problems, used to validate the code and display the capabilities of the code, are discussed. A graphical user interface is designed to pre-process the necessary data. Macros are developed for excel and Tecplot to post-process the results for easy visualization.
Keywords: Poromechanics; Modeling of porous media; Fractured porous media; Fully coupled THM model; Multiphase THM analysis; Intergrated Finite Element-Finite Volume Method; Dual Mesh-CVFE grid; Engineering, Civil (0543); Engineering, Mechanical (0548); Geotechnology (0428)